2016
DOI: 10.1016/j.jgeb.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro conservation of embryogenic cultures of date palm using osmotic mediated growth agents

Abstract: This study was carried out to investigate the effect of mannitol, sorbitol and sucrose as osmotic agents on in vitro conservation of embryogenic cultures of date palm (Phoenix dactylifera, L.) Bartamoda and Sakkoty cultivars. Embryogenic cultures was obtained using MS medium supplemented with 10 mg/l 2,4-dichlorophenoxy acetic acid (2,4-D) and 3 mg/l isopentenyl adenine (2iP). Among the three types of osmotic substances used for slow growth conservation, sucrose at all concentrations gave the highest percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…other studies have demonstrated that the presence of sorbitol and/or mannitol combined with sucrose in the conservation medium increased the survival percentage of various plant species (TAVAZZA et al, 2015;TAKUR et al, 2015;EL-BAHR et al, 2016;NASIRUDDIN AND ISLAM, 2018).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…other studies have demonstrated that the presence of sorbitol and/or mannitol combined with sucrose in the conservation medium increased the survival percentage of various plant species (TAVAZZA et al, 2015;TAKUR et al, 2015;EL-BAHR et al, 2016;NASIRUDDIN AND ISLAM, 2018).…”
Section: Resultsmentioning
confidence: 93%
“…This reduction was greater at the end of the experiment (10 months), in the presence of higher concentrations of sucrose, sorbitol or mannitol, as observed in M8 and M12, with 0.0% and 10.0% survival, respectively. osmotic agents acted as growth retardants by causing osmotic stress to the material under conservation (EL-BAHR et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we used both these methods to induce tolerance to cryopreservation in plants: before the start of the step (ii), the donor-plants were hardened on the medium with 60 g•L −1 sucrose at 8 • C for two weeks, and the excited explants were hardened on the medium enriched with sucrose (273.84 g•L −1 ) at 0-2 • C for 48 h. High sucrose in medium significantly increases cold-tolerance [44,45]. Sucrose was also used as osmotic agent, which restricts the water availability to the explant and goes about a development retardant, when added to the medium [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, for the dry mass of the roots, the smallest averages were obtained in treatments M1, M2, M3, M4, M7, M10 and M12, with respective values of 47.64 mg, 70.63 mg, 78.38 mg, 43.79 mg, 73.34 mg, 56.50 mg and 39.23 mg (Figure 3f). The decrease in the dry mass of the aerial part and roots of P. pyramidalis with reduction of osmotic potential of the culture medium can possibly be explained by the action of the osmotic agents when added to the medium, by reducing the water potential and availability of water and nutrients in the medium, inducing slower growth (Huang et al, 2014;El-Bahr et al, 2016). Therefore, the reduction in the growth of the P. pyramidalis plants, reflected in the lower dry mass values, is an advantage for in vitro conservation, where the aim is to minimize the growth of the plants to increase the interval between subcultures.…”
Section: Effect Of the Osmotic Agentsmentioning
confidence: 99%